AUTISME DALAM SERIAL DRAMA PROJECTS THE SERIES: SIDE BYSIDE - Satria Dwipayana, I Made Krisna; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2020)
Film is one of the massiimedia which is used to entertain, provide information, and other technical presentations to the generaliipublic. Film can represent and construct social realities that occur in society by using signs to describe something. ProjectiiS The Series: SideiibyiiSide is a film in the form of a series that raises the genre about autism. This research uses descriptive qualitative research by means of CharlesiiSandersiiPeirce'siisemiotic. The resultsiiofiithis studyiiindicate that this series has the ability to construct reality and describe the realities that occur in society, in this case people with autism. Therefore, in addition to being a reflection of society, this series also shows the other side of the reality of autism, where it not only has obstacles due to autism, but also has advantages that are expected to provide a new perspective on people with autism. Keywords: Charles Sanders Pierce, Semiotics, Autism, Film